2009
DOI: 10.1016/j.cell.2008.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Functional Organization of the S. cerevisiae Phosphorylation Network

Abstract: Summary Reversible protein phosphorylation is a signaling mechanism involved in all cellular processes. To create a systems view of the signaling apparatus in budding yeast, we generated an E-MAP (epistatic miniarray profile) comprised of 100,000 pair-wise, quantitative genetic interactions, including virtually all protein kinases and phosphatases and key cellular regulators. Quantitative genetic interaction mapping reveals factors working in compensatory pathways (negative genetic interactions; e.g. synthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
281
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(299 citation statements)
references
References 69 publications
16
281
2
Order By: Relevance
“…As previously suggested by genetic screens (Pan et al 2006;Collins et al 2007;Fiedler et al 2009;Costanzo et al 2010), we observed that RRM3 disruption strongly affects the growth of asf1D cells (see below). To characterize the genetic interaction between ASF1 and RRM3, one allele of ASF1 was deleted in an RRM3/rrm3D diploid.…”
Section: Loss Of Chaperone Function Of Asf1 Causes Rrm3d Lethalitysupporting
confidence: 82%
See 1 more Smart Citation
“…As previously suggested by genetic screens (Pan et al 2006;Collins et al 2007;Fiedler et al 2009;Costanzo et al 2010), we observed that RRM3 disruption strongly affects the growth of asf1D cells (see below). To characterize the genetic interaction between ASF1 and RRM3, one allele of ASF1 was deleted in an RRM3/rrm3D diploid.…”
Section: Loss Of Chaperone Function Of Asf1 Causes Rrm3d Lethalitysupporting
confidence: 82%
“…These results, showing a specific enrichment of Mms22 at forks in the absence of RRM3, are consistent with our genetic observations obtained with the Ctf4 mutants. They reinforce our conclusion that the interaction between Ctf4 and Mms22 is regulated during replicative damage and is crucial in dealing with replicative stress.Replisome destabilization allows cells lacking a functional H3K56ac pathway to survive under replicative stressTo better understand the role of H3K56ac at forks, we extended our analysis to another crucial component of the Fiedler et al 2009;Haber et al 2013), it is possible that the replicative function of MRC1 could also be deleterious in the presence of DNA damage, when H3K56ac is compromised. To test this possibility, because mrc1D is synthetic lethal with rrm3D (Naylor et al 2009), we first examined the effects of the MRC1 deletion in asf1D cells subjected to replicative stress.…”
mentioning
confidence: 99%
“…Ser/Thr/Tyr phosphorylations are ubiquitous in eukaryotes (2,50). These types of protein phosphorylations dominate eukaryotic signaling and regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Casein kinase I isoform Hrr25 not only regulates the maturation of 40 S ribosomal subunits (23), but also participates in the transcriptional response to DNA damage (24). It has been reported that Rio2 interacted with many proteins involved in ribosome biogenesis in yeast as well as proteins involved in cell proliferation (25)(26)(27)(28)(29), indicating that Rio2 may have dual functions in ribosome biogenesis and cell proliferation. However, the role of Rio2 in cell proliferation has not been addressed.…”
mentioning
confidence: 99%